뇌성마비아동의 지능검사 방법에 대한 비교 고찰 - 홍선경 (연세대학교 보건대학원, 1985)
[한글] 본 연구의 목적은 한국판 그림 지능검사인 K-PTI가 언어 및 동작장애를 가진 뇌성마비 아동의 일반적 지능을 측정하기에 타당한 측정 도구인지를 검토하는데 있다. 연구대상은 4-8세의 정상아동 30명과 언어 및 동작장애를 수반한 뇌성마비아동 30명이였고, 본 연구에 사용된 지능검사는 K-WISC와 K-PTI 이었다 일반적 지능을 측정하는데 있어서 K-PTI의 타당성은 정상아동이 K-WlSC와 K-PTI에서 획득한 지능지수의 상관관계를 산출하여 추정하였고, 뇌성마비아동의 지능측정도구로서 K-PTI의 타당성은 뇌성마비아동이 K-WlSC와 K-PTI에서 획득한 지능지수간의 차이를 통하여 추정하였다. 본 연구의 결과는 다음과 같이 요약된다. 첫째, 정상아동은 K-WISC와 K-PTI 지능지수간에 유의한 차이를 보이지 않았으나( P> .05 ), 언어 및 동작장애를 수반한 뇌성마비아동은 K-WlSC보다 K-PTI에서 유의하게 높은 지능지수를 나타냈다 ( P< .001). 둘째, K-WISC와 K-PTI 지능지수간의 상관관계에서 정상아동집단은 뇌성마비아동 집단보다 유의하게 높은 상관관계를 가졌다. 정상아동 집단에서 K-PTI 평균 지능지수는 110.80, 표준편차는 12.45이고, K-WlSC 평균 지능지수는 110.06, 표준편차는 13.25로서 높은 상관관계를 보였다(r = .95). 따라서 K-PTI는 4-8세 아동의 일반적 지능을 측정하는 도구로서 합당하다고 할 수 있겠다. 뇌성마비아동은 K-WISC보다 K-PTI에서 유의하게 높은 지능지수를 나타냈다( P< .001 ). K-PTI의 평균지능지수는 83.63, 표준편차는 11.70이였고, K-WISC의 평균 지능지수는 75.56, 표준편차는 12.27이었다. 이는 K-PTI가 언어표현과 손동작을 필요로 하지 않아서, 언어 및 동작장애를 수반한 뇌성마비아동이 K-PTI를 수행하는데 큰 지장이 없었기 때문인 것으로 추측된다. 이러한 맥락에서 볼 때 K-PTI는 뇌성마비아동의 일반적 지능을 측정하는데 비교적 타당성 있는 측정 도구가 될 것이다. A Concurrent Validity Study of the K-PTI with the K-WISC in Normal and Cerebral Palsy Children Sun Kyung Hong Graduate School of Health Science and Management Yonsei University Seoul, Korea. (Directed by Professor Jung Soon Shin, M.D.) The purpose of this study is to investigate the validity of the K-PTI (Korean Pictorial Test of Intelligence) in measuring the general intellectual ability of cerebral palsy children with language/motor Impairments. The subjects were 30 normal and 30 cerebral palsy children, respectively, aged between 4 and 8 years. The tools used to measure the subject's intelligence were the K-PTI and the K-WISC (Korean Wechsler Intelligence Scale for Children). The study was carried out between March, 1985 and May, 1985. The experimenter administered the K-PTI and the K-WISC to both normal and cerebral palsy children respectively. The IQs of the two groups on the K-PTI and the K-WISC were analyzed as follow; (1) A correlation between the normal children's IQ's measured by the K-PTI and by the K-WISC was computed: and (2) in order to investigate the validity of the K-PTI with cerebral palsy children's the cerebral palsy children's PTI IQ scores were compared with their K-WISC IQ scores. In the normal children, the correlation between the K-PTI and the K-WISC scores was 0.95. This data reveals that the K-PTI has adequate validity for measuring the general intellectual ability of normal children. In cerebral palsy children, the mean score on the K-PTI was 83.6, with a SD of 11.7, while the metro K-WISC score was 75.6 with a SD of 12.3. Therefore, in this study, cerebral palsy children's IQ on the K-PTI appeared to be significantly higher than their IQ on the K-WISC (P < .001). It is assumed that cerebral palsy children's higher IQ on the K-PTI results from the facts that the K-PTI does not require expressive language and manual manipulation of objects. Also cerebral palsy children with language and motor impairments can take the K-PTI without serious problems in responding to the questions. The results of this study suggest that the K-PTI is equally and adequately valid tn terns of measuring the intellectual abilities of both normal and cerebral pansy children. [영문] The purpose of this study is to investigate the validity of the K-PTI (Korean Pictorial Test of Intelligence) in measuring the general intellectual ability of cerebral palsy children with language/motor Impairments. The subjects were 30 normal and 30 cerebral palsy children, respectively, aged between 4 and 8 years. The tools used to measure the subject's intelligence were the K-PTI and the K-WISC (Korean Wechsler Intelligence Scale for Children). The study was carried out between March, 1985 and May, 1985. The experimenter administered the K-PTI and the K-WISC to both normal and cerebral palsy children respectively. The IQs of the two groups on the K-PTI and the K-WISC were analyzed as follow; (1) A correlation between the normal children's IQ's measured by the K-PTI and by the K-WISC was computed: and (2) in order to investigate the validity of the K-PTI with cerebral palsy children's the cerebral palsy children's PTI IQ scores were compared with their K-WISC IQ scores. In the normal children, the correlation between the K-PTI and the K-WISC scores was 0.95. This data reveals that the K-PTI has adequate validity for measuring the general intellectual ability of normal children. In cerebral palsy children, the mean score on the K-PTI was 83.6, with a SD of 11.7, while the metro K-WISC score was 75.6 with a SD of 12.3. Therefore, in this study, cerebral palsy children's IQ on the K-PTI appeared to be significantly higher than their IQ on the K-WISC (P < .001). It is assumed that cerebral palsy children's higher IQ on the K-PTI results from the facts that the K-PTI does not require expressive language and manual manipulation of objects. Also cerebral palsy children with language and motor impairments can take the K-PTI without serious problems in responding to the questions. The results of this study suggest that the K-PTI is equally and adequately valid tn terns of measuring the intellectual abilities of both normal and cerebral pansy children.
보건학과/석사